Career readiness: preparing social work students for entry into the workforce - Moore, Matt; Thaller, Jonel (Frontiers in Education, 2023)
Career readiness of college graduates is of critical importance in higher education. As defined by the National Association of Colleges and Employers (NACE, 2017), career readiness is the attainment and demonstration of requisite competencies that broadly prepare college graduates for successful transition into the workplace and/or graduate school. This article outlines the development of a sophomore-level course -Critical Thinking and Writing for Social Work Professionals -as part of a Bachelor of Social Work (BSW) program at Ball State University.The primary purpose of this course is to help students develop career readiness competencies that support their growth throughout their educational and professional social work careers. The career readiness competencies support the Educational Policy and Accreditation Standards required by the Council on Social Work Education (CSWE). The authors discuss the importance of this approach for undergraduate education and how career readiness enhances and builds upon CSWE competencies. The authors conclude with a brief discussion of student feedback and lessons learned through this process that suggests students' gained career readiness skills.